Academic self-efficacy and gender as determinants of performance in english discourse writing among high-achieving students in Ibadan, Oyo State (2015)
The study was carried out to delve into academic self-efficacy and gender as determinants of performance in English discourse writing in Ibadan, Oyo State. Descriptive survey design was adopted for the study. Purposive sampling technique was used to select 40 male and female high achieving students. Three validated instruments which are English Language Essay Screening Test (r = 0.82), English Language Essay Achievement Test (r = 0.76) and Adapted Academic Self-efficacy Scale (r = 0.76) were utilized in the study. Three research questions were answered using Pearson Product Moment Correlation and Multiple Regression Analysis. The findings revealed that academic self-efficacy had a positive relationship with performance in English discourse writing while gender had no significant correlation with the dependent variable. The independent variables had no joint effect on the dependent variable (R = .231, adjusted R2 = 0.54, P>.05). On the basis of these findings, it is recommended that educational guidance services should be made mandatory in schools as educational stakeholders should equally focus on the affective construct (self-efficacy) of high-achieving students.